Avaliação da toxicidade do agrotóxico Clorpirifós e do metal cádmio, isolados e em misturas, sobre cladóceros nativos da região neotropical - Raymundo, Larissa Broggio (2024)
The aim of this study was to assess the effects of isolated and combined concentrations of the compounds Chlorpyrifos and Cadmium on native cladocerans from tropical regions: Ceriodaphnia silvestrii, Ceriodaphnia rigaudi, and Moina micrura. To achieve this, acute toxicity tests were conducted with the isolated compounds and their combinations with C. silvestrii and C. rigaudi. Chronic toxicity tests were performed, evaluating reproduction, growth, neonate size, and immobility with C. silvestrii and C. rigaudi. Chronic tests were also conducted through different exposure routes (water, diet, and both) with M. micrura. Acute toxicity tests with Cadmium resulted in a 48-hour EC50 of 0.02 mg L-1 for C. rigaudi and 0.026 mg L-1 for C. silvestrii. The Chlorpyrifos tests yielded EC50-48h values of 0.047 μg L-1 and 0.062 μg L-1, respectively. Tests with mixtures indicated the occurrence of additive effects for C. rigaudi, whereas for C. silvestrii, antagonistic effects were observed depending on dose level. According to the Ecological Risk Assessment (ERA), Cadmium represented a high risk, while Chlorpyrifos posed insignificant to high risk. Reproduction in both species exposed to Chlorpyrifos was affected at all tested concentrations (0.0014, 0.0028, 0.0042, 0.0056, 0.0070, and 0.0140 μg L-1). Exposure to Cadmium affected the reproduction of both, C. rigaudi at all tested concentrations (0.001; 0.003; 0.005; 0.011; 0.016 and 0. mg L-1) and C. silvestrii at 0.002; 0.003; 0.005; 0.008 and 0.011 mg L-1. Neonate size produced by C. rigaudi and C. silvestrii exposed to Chlorpyrifos was affected at all tested concentrations. Cadmium exposure affected the neonate size of C. rigaudi at concentrations of 0.002; 0.005; 0.008 and 0.011mg L-1 and of C. silvestrii at 0.005; 0.011; 0.016 and 0.022 mg L-1. Growth of C. rigaudi exposed to Chlorpyrifos was affected at concentrations of 0.007 and 0.014 μg L-1, and of C. silvestrii at 0.0014, 0.0042, 0.005, 0.007, and 0.014 μg L-1. Cadmium exposure affected the growth of C. rigaudi at 0.002; 0.005; 0.008 and 0.011 mg L-1, and of C. silvestrii at 0.011; 0.016 and 0.022 mg L-1. Chronic toxicity tests on M. micrura exposed to Chlorpyrifos revealed no significant difference between treatments and the control group in terms of reproduction, growth, and feeding activity at the tested concentrations (0.14 and 0.28 μg L-1). In conclusion, both the isolated compounds and their combinations exhibited toxicity to the evaluated organisms, posing potential ecological risks to the biota of aquatic environments.